Younger Dual-Eligibles Who Use Federally Qualified Health Centers Have More Preventable Emergency Department Visits, but Some Have Fewer Hospitalizations. (January 2017) - Potter, Andrew J.; Trivedi, Amal N.; Wright, Brad
Objective: To determine whether younger dual-eligibles receiving care at federally qualified health centers (FQHCs) have lower rates of ambulatory care sensitive (ACS) hospitalization and emergency department (ED) visits.Data Sources: We used the 100% Medicare Part A and Part B institutional claims from 2007 to 2010 for dual-eligibles younger than 65 years, enrolled in traditional fee-for-service Medicare, who received care at an FQHC or lived in a primary care service area with an FQHC.Methods: Our cross-sectional analysis used negative binomial regressions to model ACS hospitalizations and ED visits as a function of prior year FQHC use. The model adjusted for beneficiary age, gender, race, and chronic diseases, as well as county fixed effects, time trends, and race-FQHC use interactions.Results: FQHC use is associated with a decrease in ACS hospitalization rates for whites (2.8 per 1000 persons), but an increase among blacks (2.5 per 1000 persons). FQHC use is also associated with an increase in ACS ED visits, from 27 to 33 more visits per 1000 persons per year, depending on patient race.Conclusions: ACS hospital use is higher for FQHC users than nonusers, but white FQHC users have fewer ACS hospitalizations. More research is needed to understand how this relationship varies within and between centers.